The Influence of Affective Image, Attractiveness, Hedonism, Psychological Well-Being, and Shopping Experience on Revisit Intention - Arifiana, Ana; Mardikaningsih, Rahayu (Airlangga Journal of Innovation Management, 2024)
This study examines the influence of affective image, attractiveness, hedonism, psychological well-being, and shopping experience on revisit intention of visitors at Tunjungan Plaza Surabaya, one of the largest and most influential shopping centers in Indonesia. By analyzing these factors, the study explores how emotional and behavioral elements impact consumer decisions to return to a shopping destination. The research was conducted using a quantitative survey method, targeting visitors who had shopped at Tunjungan Plaza within the last year. Data was collected from purposive sampling, with 207 valid responses analyzed using multiple linear regression with SPSS 27. The results show that effective image, attractiveness, hedonism, psychological well-being, and shopping experience affected revisit intention significantly. The shopping experience had the strongest impact, with all variables contributing uniquely to predicting visitor loyalty. The managerial implication includes understanding the key factors influencing revisit intentions. Management can provide facilities and services to meet the visitors’ needs and expectations. Additionally, designing shopping experiences that evoke diverse sensations and utilizing technological advancements can improve customer satisfaction. Management should also create a fun and engaging atmosphere to reduce stress and boredom among visitors. This study provides new insights into the dynamics of visitor behavior in the context of shopping malls, especially in developing countries like Indonesia. It highlights the critical role of emotional and experiential factors in influencing customer loyalty and revisitation to shopping centers.